Land Potential for Cacao (Theobroma cacao. L) Development in Banggai Regency: Land potential for cocoa development in Banggai Regency - Muh.Zamalluddin M Stibis; Mihwan Sataral; Dian Puspapratiwi (CELEBES Agricultural, 2022)
Seeing the bright prospects of cacao plants with the available land potential in Banggai Regency, it is necessary to assess land suitability in the development of cacao plants to know the actual potential land suitability level and the limiting factors that affect the potential for cacao plant development, apart from that it can optimize land use in the area, Banggai Regency. The approach used as an indicator for determining the land suitability class for cacao plantations in Banggai Regency is to take an FAO parametric index land quality based on land characteristics that match the requirements for land use for cacao plants, then tabulated into land map units. The results show that the actual land suitability class of Banggai Regency is N = not suitable and S3 = marginally suitable, with the limiting factor of water availability, root media, nutrient retention, available nutrients, and erosion hazard. So that land improvement efforts are needed to increase the land suitability class by considering the existing potential. Improvement efforts that can be done include adding lime, fertilizer, and organic matter, making mound terraces, bench terraces, credit terraces, and erosion-retaining plants. So that the results of the potential land suitability class are S1 = very suitable, S2 = suitable, S3 = marginally suitable, with an area of ​​land that can be developed for cacao plants in Banggai Regency, namely 419,236.9 ha.